2011
DOI: 10.2527/jas.2010-3308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and Aspergillus oryzae extract or Saccharomyces cervisiae on growth and carcass characteristics of lambs and steers fed to meet requirements of natural markets1,2

Abstract: Two studies were conducted to determine the effects of diet and feed additive on growth and carcass characteristics of lambs and cattle destined for all natural markets. In Exp. 1, 48 Dorset × Hampshire lambs (initial BW 29.4 ± 0.1 kg) were used in a randomized complete block experiment to determine the effects of Aspergillus oryzae extract, Amaferm (AMF) supplementation (1 g/d) in an 85% concentrate diet on growth and carcass characteristics. Lambs were allotted to 12 pens (4 lambs per pen), and blocked by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(40 reference statements)
3
11
0
Order By: Relevance
“…As discussed previously, the effect of YC supplementation, alone (not enriched with Cr), on carcass characteristics (Jones et al 1997;Kawas et al 2007;Payandeh and Kafilzadeh 2007;Titi et al 2008;Zerby et al 2011), wholesale cuts (Titi et al 2008;Whitley et al 2009), or visceral mass (Belewu and Jimoh 2005) of feedlot lambs has been small and non-appreciable. Thus, is expected that the changes in carcass measures in the present experiment are more directly related to Cr intake, per se.…”
Section: Itemmentioning
confidence: 87%
See 1 more Smart Citation
“…As discussed previously, the effect of YC supplementation, alone (not enriched with Cr), on carcass characteristics (Jones et al 1997;Kawas et al 2007;Payandeh and Kafilzadeh 2007;Titi et al 2008;Zerby et al 2011), wholesale cuts (Titi et al 2008;Whitley et al 2009), or visceral mass (Belewu and Jimoh 2005) of feedlot lambs has been small and non-appreciable. Thus, is expected that the changes in carcass measures in the present experiment are more directly related to Cr intake, per se.…”
Section: Itemmentioning
confidence: 87%
“…Likewise, Adams et al (1981) reported no differences in DMI of lambs fed a 50 : 50 forage : concentrate diet supplemented with 2.5% of live yeast (targeted 20 g/lamb.day of S. cerevisiae) during a 73-day growing-finishing period. Supplemental Aspergillus oryzae (1 g/day) did not affect DMI of lambs fed a high-energy finishing diet during a 72-day period (Zerby et al 2011). In steers, supplementation with 10 g/day YC did not affect the DMI of steers fed a 74% barley-based finishing diet (Mir and Mir 1994).…”
Section: Dry Matter Intakementioning
confidence: 89%
“…It can be used as a prebiotic in calf feed (Beharka et al, 1991), but has more commonly been used in sheep and beef finishing diets (Schmidt et al, 2004;Zerby et al, 2011). Aspergillus oryzae has long been used in the Japanese food industry for fermenting foods such as saki, soy sauce, and miso, and it is regarded as safe because it does not produce aflatoxin (Uchida et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Specific strains of bacteria are used for this purpose in animal feed (Donohue 2006). In beef cattle production systems, antibiotics are used to decrease the frequency of metabolic disorders, improve efficiency, and reduce ruminal acidosis, however, the use of some unnatural antibiotics is restricted (Zerby et al 2011). Some bacterial species of the genera Lactobacillus and Bifidobacterium have been shown to have good results as probiotics in ruminants, increasing levels of weight gain and efficiency (Whitley et al 2009).…”
Section: Use Of Microorganism Fermentation Activatorsmentioning
confidence: 99%